Pengaruh Model Collaborative Learning dengan Media Artificial Intelligence Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa SMA di Kawasan Sekolah Agroekosistem - Nur Mualifatun Azizah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the low level of students’ critical thinking skills and learning outcomes, which are still dominated by conventional learning. Limited student engagement, and the suboptimal use of this study was to analyze the effect of the Collaborative Learning model assisted by Artificial Intelligence on the critical thinking skills and learning outcomes of senior high school students. A quasi-experimental method was employed involving two tenth-grade classes at SMA Negeri Pakusari using random sampling techniques, where one class served as the experimental group and the other as the control group. The instruments used included cognitive tests in the form of pretest and posttest, affective assessments using observation sheets, and critical thinking tests in the form of descriptive questions based in Ennis’s indicators. The experimental class was taught using the Collaborative Learning model supported by Artificial Intelligence in the form of ChatGPT, while the control class was taught using conventional learning methods. The results showed significant differences with p < 0,05 for both critical thinking skills and student learning outcomes. It can be concluded that the Collaborative Learning model assisted by Artificial Intelligence has significant effect on students’ critical thinking skills and learning outcomes. Students who learned using this model were better able to develop intellectual skills through group discussions, exchanging ideas, and analyzing various perspectives in problem-solving compared to those who learned through conventional methods.
Reva_21 Mei 2026
Keywords: collaborative learning; critical thinking; learning method; learning outcomes